Analysis of the Distribution of Justice on the Economic Meaning of Inheritance of Property in the Perspective of Islamic Business Ethics - Imam Muttaqin, Faruqi; Anwar, Syahrul; Kania, Dede (Yayasan Mentari Madani, 2024)
This article conducts an in-depth analysis of the distribution of justice in the context of inheritance of property in Islam, with a focus on the economic meaning and perspective of Islamic business ethics. The discussion includes the basic principles of inheritance according to sharia, the economic implications of the distribution of inherited assets, and the application of Islamic business ethics values in the inheritance process. The concept of justice, as explained in Islamic teachings, is the main pillar in determining how inherited assets are divided fairly among heirs. Inheritance of assets not only contains economic value as an investment resource, but is also a reflection of social responsibility and Islamic business ethics. Through case study analysis and evaluation of the impact of distribution of justice, this article concludes that integrating Islamic values in the inheritance of assets can create a society that is just, economically dynamic, and in accordance with the principles of Islamic business ethics